2021
DOI: 10.1177/00405175211023813
|View full text |Cite
|
Sign up to set email alerts
|

Development of aldehyde and similar-to-aldehyde tanning agents

Abstract: Aldehyde and similar-to-aldehyde tanning agents were used in oil tanning and smoke tanning in ancient times. The aldehyde group reacts with the protein amino group in electrophilic form to obtain the preservation stability and practical function of fur and leather. The results showed that aldehyde-tanned leather can promote the hydrothermal stability of skin collagen and has better water and sweat resistance properties than chrome tanning. However, aldehyde tanning agents always lack sufficient coulombic attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The peak half width increase may be explained by OSA’s variable molecular mass. The very slight differences between the values of the denaturation enthalpy of the glutaraldehyde-tanned and OSA-tanned samples suggest both tannins appear to have the same type of chemical interactions with the collagen in the collagen matrix [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peak half width increase may be explained by OSA’s variable molecular mass. The very slight differences between the values of the denaturation enthalpy of the glutaraldehyde-tanned and OSA-tanned samples suggest both tannins appear to have the same type of chemical interactions with the collagen in the collagen matrix [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…As aldehydes do not have any ionic groups, they cannot be adsorbed readily into collagen by electrostatic attraction, resulting in very poor adsorption into collagen and producing inferior performance. Moreover, aldehyde tanning agents are not only biotoxic but also they are poorly soluble in water and costly, 155 and the treated leather releases formaldehyde during use, which is a Class 3 carcinogen. 156 It was also reported that formaldehyde is released not only from aldehyde-tanned leather but also from THPS-tanned leather.…”
Section: Sustainable and Eco-friendly Chromefree Tanning Processesmentioning
confidence: 99%
“…To keep our environment safe from pollution and to reduce health risks for workers in tannery industries, many attempts were made to avoid the application of chromium compounds in tanning https://doi.org/10.31881/TLR.2024.036 processes. Different alternative tanning materials such as vegetable tannins, oils, aldehyde tannins, zirconium tannins, aluminium tannins, titanium tannins, polymer tannins, amino acids, etc., were used in tanning operations [20][21][22]. However, these alternating tanning agents showed many limitations in tanning processes and they did not work effectively like chromium compounds thus the entire replacement of chromium with a viable alternative material was not found to be feasible in tannery industries [22].…”
Section: Introductionmentioning
confidence: 99%